THE DECLINE OF INNOVATIVE LOCAL SELF-GOVERNANCE INSTITUTIONS FOR WATER MANAGEMENT: THE CASE OF PANI PANCHAYATS - Ganesh B. Keremane Jennifer McKay and Narayanamoorthy (International Journal of Rural Management 2(1), 2006, 2006)
Water scarcity to a large extent is manmade and large irrigation projects are seen as a solution to the problems of water scarcity. But the solution to the problems that such scarcity generates lies in recognizing the fact that water is a common resource and can be managed sustainably, based on the principles of local and collective self-management. India has a rich history of indigenous systems of water management, some of which are still in use even after thousands of years. Pani Panchayats in Maharashtra are examples of such indigenous self-governance institutions formed for ecological and equitable use of water on the basis of collective control and decision making. But, today, these innovative institutions have collapsed due to various reasons. A study funded by the Australian Center for International Agricultural Research (ACIAR) was carried out to identify the reasons for the decline of Pani Panchayats from a farmer's perspective. The results revealed that lack of effective institutional protocol to enforce the rules to govern water use, resolving the conflicts, accompanied by lack of support from the government and other agencies are the major reasons for the decline